Optical Dating of Quartz Grains From the Minjiang Fluvial Terraces in the Sonpan Area on the Eastern Margin of the Tibetan Plateau - Han, Ye-Song; Zhang, Jia-Fu; Liu, Geng-Nian; Cui, Zhi-Jiu (Frontiers in Earth Science, 2022)
The fluvial terraces along the banks of the Minjiang River are very important for understanding the tectonic activities of the eastern margin of the Tibetan Plateau and have been widely investigated. However, the reliability of the ages previously reported for the terraces needs further evaluation. In this study, the Minjiang River terraces in the Sonpan area from Hongqiaoguan to the Songpan town were investigated and dated using optically stimulated luminescence (OSL) techniques on quartz grains. Seven strath terraces (T1–T7) were recognized based on the exposures of fluvial sediment and the elevation of bedrock strath, and two of them have been reported by previous studies. The terrace deposits and overlying loess were sampled for OSL dating. The samples exhibited a large scatter in De, even for loess samples, which could be attributed to poor bleaching at deposition. However, the OSL ages obtained using the minimum age model were underestimated, and those obtained using the central age model are considered relatively reliable based on stratigraphic and geomorphological consistency and the comparison of the ages between stratigraphically parallel samples. The results show that the loess samples overlying fluvial terrace sediments were deposited later than terrace formation and their OSL ages cannot represent the terrace formation ages. The T1, T3, T4, T5, and T6 terraces were dated to 13.5±0.6, 29.0±1.8, 48.0±3.3, 44.3±5.2 and 63.8±4.7ka, respectively. The T4 and T5 terraces may be the same terrace with a weighted mean age of 46.9±2.8 ka. The ages of the T2 and T7 terraces were inferred to be ~20 and ~80 ka, respectively, based on the relationship between strath ages and elevations of the other terraces. The mean bedrock river incision rates were calculated to be 1.2 ± 0.1 mm/a for the time period of 63 ka for the T6 terrace – 14 ka for the T1 terrace, and 0.15 mm/a for the past 14 ka.